Organizational forms and valuation framework of data factor market - Chuanwei ZOU (大数据)
The organizational forms and valuation framework of data factor market are two important questions in developing and regulating data factor market.To solve these two problems, the idea that clear ownership is not a necessary condition for data factor market to function efficiently was argued.Rather, effective control of data factor is more important.Based the similarities between data factor market and financial system, possible organizational forms of data factor market were suggested.Lastly, a new framework of data factor valuation, DataRank, was proposed, to reflect the subjectivity, time-variance, and externality of data factor value better.